(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
Whilst there has been an increasing recognition that public transport systems are complex systems Lu and Shi (2007); (Pezzillo Iacono, Mangia, Canonico, & De Nito, 2010; Sienkiewicz & Hołyst, 2005) and therefore require of complex systems approaches to their analysis and design, there is not yet many examples in the literature to illustrate how this could be done and which would the learning be of taking such analytical approach. To contribute in this research path, this article analyses the trunk component of the Integrated Public Transport System of Bogotá (IPTS) as a business ecosystem, from the perspective of the Viable System Model (VSM). We first present the conceptual bases of the VSM and then present the methodological fundamentals to model the ITPS as a complex system under this chosen optics. Following a longitudinal analysis approach, we then model the complexity of the IPTS – and its environmental niche over the last 15 years since its inception. This preliminary analysis indicates that the development of the IPTS has not coped well with the variety of the urban development, so the IPTS does not exhibit requisite variety. A heuristic to continue this type of analysis is suggested that allows strategic systems’ design and re-development, based on this model. Finally, we present our reflections about how this research path respond to existing questions in the literature in public transport systems and OR.